Die rol en taak van die kerk ten opsigte van begrafnisgebruike - Oliver, E. (Verbum et ecclesia, 2007)
The modern trend to keep death at a distance has a negative impact on Christians. It seems as if the Church is following this societal pattern and is incompetent to provide sufficient information and preparation to church members. This can be one of the reasons why people who are confronted by the trauma of death, are not able to coupe or find comfort and security in their faith. The historical development of funeral rites, as well as the viewpoint of the different South African sister churches regarding funerals, are responsible for the current gap in ministry to the bereaved. This gap can be filled by redirecting the theological focus of the church, also by providing information, training and guidance to both church members and support groups, and by reforming funeral rites.